DEVELOPMENT OF LIVE WORKSHEET-BASED CRI INSTRUMENTS TO DETECT STUDENT MISCONCEPTIONS ON STRAIGHT LINE MOTION MATERIALS - Ayu Cintana Asri; Muhammad Taufiq (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2022)
This research aims are to develop and test the validity of the diagnostic assessment instrument of misconceptions on the motion concept through CRI (Certainty of Response Index) Live Worksheet-based. The test questions were carried out by 23 students of class VIIIB SMP Setiabudhi Semarang. This research instrument uses the Research and Development method of the 4-D development model from Thiagarajan. The validity of this study was carried out using expert validation and item analysis. In the expert validation stage, the question instrument was validated by 3 validators consisting of evaluation experts and material experts with an average proportion of 93.59%. The questions were tested on 20 students, and it was stated that there were 15 questions. The data obtained were analyzed with the help of the Anates application version 4.09. The results showed that: (1) Based on the criteria for the level of difficulty obtained from 1 item (5%), moderate 16 items (80%), difficult 3 items (15%); (2) Based on the question criteria, it was obtained very low 2 items (10%), low 1 item (5%), moderate 10 items (50%), and high 7 items (35%); (3) Based on the reliability test, it was found that the reliability of the test of 0.77 in the high category. Based on the analysis of research data that has been carried out, it can be concluded that the diagnostic test evaluation tool in the form of multiple choice based on the Certainty Response Index (CRI) with predetermined reasons can be used to identify students' misconceptions in straight motion material. The level of misconceptions experienced by grade VIII students of SMP Setiabudhi Semarang consists of the cognitive domains C1-C5. At the level of understanding C1 with 4.4% misconception, C2 28.7%, C3 33.5%, C4 27.1% and C5 6.3%. This research is expected to be a reference or consideration as a form of instrument based on misconceptions on the Straight Motion material through the Live Worksheet-based CRI model.Keywords: CRI Instruments; Live Worksheets; Misconceptions; Straight Motion; Validity.